515 Use of urinary biomarkers and bioassays to evaluate chemical exposure and activation of cancer pathways in firefighters. (24th April 2018) - Hoppe-Jones, C; Beitel, S; Burgess, JL; Snyder, S; Flahr, L; Griffin, S; Littau, S; Jeong, KS; Zhou, J; Gulotta, J; Moore, P
Abstract : Introduction: Cancer is a leading cause of fire service morbidity and mortality. Measurement of urinary polycyclic aromatic hydrocarbons (PAHs), a group which includes known carcinogens, provides a means of evaluating absorption from all exposure routes. Activation of the aryl hydrocarbon receptor (AhR) and p53 pathways is associated with cancer, and their evaluation through in vitro urinary bioassays provides measures of toxicity of the chemical mixtures to which firefighters are exposed. Methods: Urine was collected at baseline and two hours after responding to fires in 80 Tucson firefighters. Urine contaminants were de-conjugated using β-Glucuronidase and extracted using Focus Solid Phase Extraction (SPE) cartridges. Quantification of hydroxylated PAH (PAH-OH) target analytes was conducted with GC-MS/MS. In addition, the urinary extracts were evaluated using AhR and p53 in vitro bioassays. Results: Compared to baseline, structural firefighting was associated with an increase in urinary PAH-OH concentrations. Increased concentrations were also found in training fires when self-contained breathing apparatus (SCBA) were used assiduously, suggesting a primary route of dermal exposure in that setting. Contrary to expectations, engineers (vehicle drivers) also demonstrated increased urinary PAH-OH concentrations, which was felt to be due to inhalation exposure as they generally did not wear SCBA. AhR and p53 activation occurred in general with higher concentrations of PAH-OHs in the urine, but extent of activation was not highly correlated with any single urinary PAH-OH marker. Conclusion: Among firefighters, urinary PAH-OH concentrations increase in both entry teams and engineers. The route and extent of dermal and inhalation exposure vary with the specific job task at the fireground. AhR and p53 in vitro bioassays demonstrate activation of cancer pathways following occupational exposure in firefighters.